2022
DOI: 10.1186/s12958-022-01018-w
|View full text |Cite
|
Sign up to set email alerts
|

Delayed puberty, gonadotropin abnormalities and subfertility in male Padi2/Padi4 double knockout mice

Abstract: Background Peptidylarginine deiminase enzymes (PADs) convert arginine residues to citrulline in a process called citrullination or deimination. Recently, two PADs, PAD2 and PAD4, have been linked to hormone signaling in vitro and the goal of this study was to test for links between PAD2/PAD4 and hormone signaling in vivo. Methods Preliminary analysis of Padi2 and Padi4 single knockout (SKO) mice did not find any overt reproductive defects and we pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 74 publications
(64 reference statements)
2
4
0
Order By: Relevance
“…To verify the identity of the relatively weak PADI2α immunoreactivity seen on western blot, we repeated the experiment using differentiated oligodendrocytes, a setting where the baseline expression of Padi2α is increased (electronic supplementary material, figure S1b-d). We found that PADI2α was firmly expressed in differentiated oligodendrocytes, confirming the previously demonstrated [12,[32][33][34][35] specificity of the PADI2 antibody (electronic supplementary material, figure S1e). 3b,c).…”
Section: (B) Padi2β Is Unstable Yet Inhibits Oligodendrocyte Differen...supporting
confidence: 89%
See 1 more Smart Citation
“…To verify the identity of the relatively weak PADI2α immunoreactivity seen on western blot, we repeated the experiment using differentiated oligodendrocytes, a setting where the baseline expression of Padi2α is increased (electronic supplementary material, figure S1b-d). We found that PADI2α was firmly expressed in differentiated oligodendrocytes, confirming the previously demonstrated [12,[32][33][34][35] specificity of the PADI2 antibody (electronic supplementary material, figure S1e). 3b,c).…”
Section: (B) Padi2β Is Unstable Yet Inhibits Oligodendrocyte Differen...supporting
confidence: 89%
“…Arguing that expression of PADI2β could inhibit oligodendrocyte differentiation by balancing the action of PADI2α, we generated a PADI2β-overexpressing oligodendrocyte precursor cell line [31]. Comparing PADI2α and PADI2β protein levels, using a previously published antibody able to faithfully capture both PADI2 overexpression and knock out [12,3235], revealed enrichment of PADI2α but not PADI2β, neither in control nor in PADI2β-overexpressing cells (figure 2 d , 0 h). Reasoning that PADI2β could be rapidly degraded, we added a proteasome inhibitor for 6, 10 or 24 h to both control and PADI2β-overexpressing oligodendrocyte precursors.…”
Section: Resultsmentioning
confidence: 99%
“…Mice are weaned around P21, and soon after, between P21 and P23 mice enter adolescence ( Brust et al, 2015 ; Figure 2 ). The onset of puberty is defined by vaginal opening in females and balano-preputial separation in males and is reached around P26 in females and about P30 in males ( Safranski et al, 1993 ; Chehab et al, 1997 ; Brust et al, 2015 ; Sams et al, 2022 ), although sexual reproduction might be only achieved a few days later, after maturation of the genitalia and gametes ( Safranski et al, 1993 ; Brust et al, 2015 ; Vidal, 2017 ). Post-puberal adolescence will encompass physiological, neurological and behavioral changes leading to sexual maturity, i.e., intratesticular testosterone in males reaches adult levels ( Keene et al, 2002 ), and females are sexually and behaviorally mature to mate and raise offspring successfully ( Brust et al, 2015 ).…”
Section: When Are Mice and Rats Adults?mentioning
confidence: 99%
“…Alternatively, the mechanisms regulating the secretion of IgA and IgM may differ between mouse and human plasmablasts. Examining B cells derived from mice deficient in both PAD2 and PAD4 ( 32 ) will help distinguish these two scenarios.…”
Section: Discussionmentioning
confidence: 99%